Comparison of hematological parameters between single and twin pregnancies in Dorper ewes during gestation, lambing, and postpartum - Santarosa, Bianca Paola [UNESP]; Dantas, Gabriela Nascimento [UNESP]; Ferreira, Danilo Otávio Laurenti; Hooper, Henrique Barbosa; Porto, Ana Carolina Rusca Correa; Garcia, Silvia Maria França Carvalho; Surian, Soraya Regina Sacco; Pieruzzi, Paula Adriane Piccolo; Silva, Andreza Amaral Da; Gonçalves, Roberto Calderon [UNESP] (Universidade Federal de Santa Maria, 2021)
The hematopoietic system changes during the pregnancy to carry fetal development and maternal needs. This study compared the hematological parameters between ewes with single and twin pregnancies during gestation, delivery, and postpartum. The experiment was conducted on 60 healthy pregnant Dorper ewes that were divided into two experimental groups: Group 1 (G1), with single pregnancies (n=30), and Group 2 (G2), with twin pregnancies (n=30). Blood samples were collected from all ewes at different times: immediately before fixed-time artificial insemination (AI); on day 30, 90, 120, 130, and 140 of pregnancy; immediately after delivery; and at 24h and 48h postpartum. Statistical analysis compared the two groups at different times (P<0.05). Mild, normocytic, and hypochromic anemia was detected in all ewes from AI time and throughout pregnancy from both groups, but did not prove to be of clinical relevance. In the peripartum stage (from the 140th day of pregnancy to 48h postpartum), the ewes with twin pregnancies (G2) exhibited higher erythrogram values and neutrophil:lymphocyte ratio than did ewes with single pregnancies (G1). This indicated a greater hematopoietic adaptation in the body during the development of two fetuses. Except for the eosinophil numbers, all leukogram parameters were influenced by pregnancy in a similar way in both groups, and was characterized mainly by leukocytosis with neutrophilia during peripartum due to the high presence of endogenous cortisol at delivery. Thus, these findings showed that pregnancy was a stressful physiological event that increased the leukocyte count with a slight alteration in the erythrogram of Dorper ewes.

O sistema hematopoiético sofre mudanças durante a gestação para atender o desenvolvimento fetal e as necessidades maternas. Este estudo comparou os parâmetros hematológicos entre ovelhas com gestação simples e gemelar durante a prenhez, parto e pós-parto. O estudo foi realizado em 60 ovelhas Dorper prenhes, saudáveis, divididas em dois grupos experimentais: Grupo 1 (G1) com gestação simples (n = 30); e Grupo 2 (G2) com gestação gemelar (n = 30). Amostras de sangue foram colhidos de todas as ovelhas em diferentes momentos: imediatamente antes da inseminação artificial em tempo fixo (IA); nos dias 30, 90, 120, 130 e 140 de gestação; imediatamente após o parto; e às 24h e 48h pós-parto. A análise estatística comparou os dois grupos nos diferentes momentos (P < 0,05). Anemia leve, normocítica e hipocrômica foi detectada desde a IA e ao longo da gestação, nas ovelhas de ambos os grupos, mas não houve relevância clínica. Na fase periparto (do 140º dia de gestação às 48h pós-parto), as ovelhas com gestação gemelar (G2) mostraram valores do eritrograma e proporção neutrófilos: linfócitos mais elevados do que as ovelhas com gestação simples (G1). Isso indicou maior adaptação hematopoiética da ovelha para o desenvolvimento de dois fetos. Com exceção do número de eosinófilos, todos os parâmetros do leucograma foram influenciados pela gestação de forma semelhante em ambos os grupos, e foi caracterizada principalmente por leucocitose com neutrofilia no periparto devido ao alto nível de cortisol endógeno no parto. Assim, os achados mostraram que a gestação foi um evento fisiológico estressante que aumentou a contagem de leucócitos com leve alteração no eritrograma de ovelhas Dorper.
Comparação dos parâmetros hematológicos entre ovelhas Dorper de gestação simples e gemelar durante a prenhez, parto e pós-parto
Keywords: erythrogram; hematology; leukogram; single and twin pregnancies; sheep; eritrograma; gestação simples e gemelar; hematologia; leucograma; ovinos